Studi Komparatif Tarjamah Tafsiriyah karya Quraish Shihab dan Muhammad Thalib - Habib Arpaja; Azhari Andi (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2024)
This study compares the Qur'an and its meaning by M. Quraish Shihab with Tarjamah Tafsiriyah by Muhammad Talib. Theoretically and methodologically, both use the tafsiriyah or ma'nawiyah translation method, but the results of the translation are different. The emergence of these two works was due to the legal polemic of the translation of the Qur'an and their criticism of the Ministry of Religion's translation of the Qur'an. This research is library research. The data obtained were processed by descriptive-comparative-analytic method. The results of the study show that in translating the verses of Aqidah, Syari'ah and Mu'amalah, there is no significant difference between the Qur'an and its Meaning by M. Quraish Shihab and Tarjamah Tafsiriyah by Muhamamd Talib. The only difference that stands out is the style of language and the form of the Tafsiriyah translation between the two. Another difference lies in the source of the translation reference, Muhammad Talib refers to the commentary of classical scholars. Meanwhile, M. Quraish Shihab's translation only comes from one book of commentary, namely Tafsir Muntakhab by Egyptian experts. The advantages and disadvantages are in the steps of the translation method, the benchmark for the correctness of Muhammad Thalib's translation looks at 8 aspects, namely Indonesian grammar, Indonesian logic, Arabic literature, asbabun nuzul verse, meaning of verses, aqidah, sharia, mu'amalah. Meanwhile, M. Quraish Shihab refers to the fatwa of the scholars of al-Azhar, Egypt. The difference in translation between M. Quraish Shihab and Muhammad Talib has implications for differences in understanding the content of verses of the Qur'an such as Surah Hud verse 107 and Surah al-Fatihah verse 1, it can be seen that M. Quraish Shihab is tolerant to non-Muslims when translating words. ar-Rahman and ar-Rahim. In the shari'ah verses of Surah al-Ahzab verses 49 and 52, it is found that the translation of M. Quraish Shihab and Muhammad Talib is very tolerant of divorce cases.